EVOLUTION OF MEADOW SAZ SOILS OF THE EASTERN PARTS OF THE FERGANA VALLEY UNDER THE INFLUENCE OF ANTHROPOGENIC FACTORS (Web of Technology: Multidimensional Research Journal, 2025)
The article highlights the role of anthropogenic factors in the process of modern evolutionary development of irrigated meadow-saz soils of Eastern Fergana.